Comparative policies of cultural tourism in times of crisis - Martorell Carreño, Alberto (2018)
It is a fact that 21st Century arrived in the middle of crises which demand our reflections and work to solve them. Human mobilization processes have reached unsuspected levels. Violence is still a strong factor present in international relationships. Cross-border economic crises have shown the darkest side of globalization: cross-border corruption. Tourism is facing these problems permanently. But it also nourishes from contemporary developments: fastest transportation systems, instantaneity of communications that make information flowing  each and everywhere, becoming a so usual phenomenon that we do not consider it any estrange process. Tourism implies facing the “others”. If we understand tourism positively, if we focus on it as an ally and not an enemy, if those visiting different cultures respect them, and they receive him/her with interest and curiosity, tourism can become a very important tool for the construction of peace and mutual comprehension. If it is the opposite, tourism can open the door for real and intense difficulties. Is tourism a tool to multiculturalism, the construction of common spaces, a road to peace?